THE REFLECTION OF ATTITUDE CHANGE IN ANTON CHEKOV’S STORY “FAT AND THIN” - Arianto, Tomi; Septriani, Septriani (eScience Humanity Journal, 2023)
This study aim to reveal the attitude change that are reflected through the story character written by Anton Chekov entitled “Fat and Thin”. Anton Chekov with his high-level imaginative mind can use narration in criticizing human behavior, especially the vertical nature of Russian society which likes to serve itself in positions and titles which are also known as "bootlickers". Changes in attitudes like this have even become a dilemma almost shared by many people around the world. This literary criticism is then explored more deeply by using the attitude change approach in psychology from Carl Hovland supported by the balance Heider theory. The method used in this research is a descriptive qualitative method with data collection and analysis techniques in librarian study. The results of this research indicated that the reflection of attitude change through the behavior of the two friends who are called fat and thin in the story. The two of them are childhood friends who have not seen each other for a long time. The change in attitude was evident from Thin's attitude, who knew that Fat was his military superior with the rank of lieutenant general. Such a situation makes Thin's behavior change a form of balancing as a defense mechanism of conditions. Chekhov, through his clear naration and dialogues, displayed this behavior very strongly. There are several factors that cause this change in attitude including psychological internal factors in the form of mental discomfort and personal dissonance, as well as external factors that influence in the form of interactions, situations and targets. This story describes an inner relationship because an idealistic friendship changes in attitude due to the vertical relationship factor that places a person as a bootlicker.